2006
DOI: 10.1039/b606622b
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Lanthanide compounds for therapeutic and diagnostic applications

Abstract: The medical applications of lanthanides are diverse: MRI contrast agents, hypophosphatemic agents for kidney dialysis patients, luminescent probes in cell studies, and for palliation of bone pain in osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Nanoparticles or nanorods have been widely used for useful research tools, advanced drug delivery systems (DDS), and new ways to detect and treat disease or repair damaged tissues and cells (Alivisatos et al , 1996; Bruchez et al , 1998; Parak et al , 2003; Alivisatos, 2004; Gao et al , 2004; Thrall, 2004; Gao et al , 2005; Jain, 2005a; Jain, 2005b; Medintz et al , 2005; Michalet et al , 2005; Prescher and Bertozzi, 2005; Patra et al , 2008a; Patra et al , 2008b; Patra et al , 2008c). In this context, several groups including our group have demonstrated that lanthanide (Eu, Tb, Gd) elements/nanoparticles play important roles in biology and medicine due to their unique physical, chemical, and electronic properties (Misra et al , 2004; Sigel and Sigel, 2004; Authors, 2006; Patra et al , 2006; Thompson and Orvig, 2006; Yu et al , 2006; Patra et al , 2007; Patra et al , 2008b; Patra et al , 2009). Recently, we have demonstrated that europium hydroxide [Eu III (OH) 3 ] nanorods (inorganic nanorods) exhibit significant pro-angiogenic activities (Patra et al , 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles or nanorods have been widely used for useful research tools, advanced drug delivery systems (DDS), and new ways to detect and treat disease or repair damaged tissues and cells (Alivisatos et al , 1996; Bruchez et al , 1998; Parak et al , 2003; Alivisatos, 2004; Gao et al , 2004; Thrall, 2004; Gao et al , 2005; Jain, 2005a; Jain, 2005b; Medintz et al , 2005; Michalet et al , 2005; Prescher and Bertozzi, 2005; Patra et al , 2008a; Patra et al , 2008b; Patra et al , 2008c). In this context, several groups including our group have demonstrated that lanthanide (Eu, Tb, Gd) elements/nanoparticles play important roles in biology and medicine due to their unique physical, chemical, and electronic properties (Misra et al , 2004; Sigel and Sigel, 2004; Authors, 2006; Patra et al , 2006; Thompson and Orvig, 2006; Yu et al , 2006; Patra et al , 2007; Patra et al , 2008b; Patra et al , 2009). Recently, we have demonstrated that europium hydroxide [Eu III (OH) 3 ] nanorods (inorganic nanorods) exhibit significant pro-angiogenic activities (Patra et al , 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Cationic lanthanum (La 3+ ) also binds to the G protein‐coupled CaR and may affect the osteoblast‐like differentiation in VSMCs. In recent years, lanthanide compounds have attracted intensive research interest in medical applications [Fricker, 2006; Thompson and Orvig, 2006]. Lanthanum carbonate is currently used in the treatment of hyperphosphatemia of chronic renal failure [Berns and Korbin, 2006].…”
mentioning
confidence: 99%
“…Such is the diversity of this field that their application reaches from magnetic resonance imaging and cell labelling 1,2 , to potential building blocks of quantum computers 3 . The pursuit of such applications relies on detailed knowledge of the magnetic anisotropy, which, while being completely defined in cases of high symmetry, is difficult to elucidate in low-symmetry complexes.…”
mentioning
confidence: 99%